Exploring correlations between anatomic characteristics of dialysis arteriovenous fistula stenosis and arteriovenous fistula blood flow rate (Qa). Issue 1 (January 2020) - Nassar, George M; Beathard, Gerald
Background: Radiologic justification for endovascular treatment of a dialysis arteriovenous fistula circuit stenosis is currently based on ⩾50% severity. However, the clinical significance of any given stenosis is not always clear. The minimum luminal diameter of any stenotic lesion in the arteriovenous fistula circuit might exert a more predictive effect on the arteriovenous fistula blood flow rate (Qa). Methods: To investigate relationships between anatomic parameters of stenosis and Qa, this study was conducted in a cohort of patients with a variety of arteriovenous fistula stenotic lesions. The goals were to determine (1) the degree of correlation between arteriovenous fistula stenosis estimated during the procedure, and that which is measured, and (2) the correlations between two anatomic stenosis parameters (percent stenosis and stenosis minimum luminal diameter) and Qa. Results: The cohort comprised 113 patients. Only a moderate correlation between estimated and measured stenosis was seen. A correlation between measured stenosis and Qa for the whole cohort was not seen, but a weak correlation between estimated stenosis and Qa was seen. Correlations between stenosis minimum luminal diameter and Qa were superior. The superiority of stenosis minimum luminal diameter to percent stenosis in correlating with a Qa of <500 mL/h was also demonstrated by receiver operating characteristics curve analysis. Stenosis minimum luminal diameter cutoffs of ⩽2.5 mm or >4 mm seemed to have a good predictive value of Qa. Conclusions: Percent stenosis determination is fraught with uncertainty and exhibits a weak correlation with Qa. Compared with percent stenosis, the minimum luminal diameter of the stenosis demonstrates a superior correlation with Qa.